2021
DOI: 10.1182/bloodadvances.2021004423
|View full text |Cite
|
Sign up to set email alerts
|

Search for AL amyloidosis risk factors using Mendelian randomization

Abstract: In amyloid light chain (AL) amyloidosis, amyloid fibrils derived from immunoglobulin light chain are deposited in many organs, interfering with their function. The etiology of AL amyloidosis is poorly understood. Summary data from genome-wide association studies (GWASs) of multiple phenotypes can be exploited by Mendelian randomization (MR) methodology to search for factors influencing AL amyloidosis risk. We performed a 2-sample MR analyzing 72 phenotypes, proxied by 3461 genetic variants, and summary genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Literature review also indicated that functions of 17G-subtype1 and 13G-subtype2 were related to features of their corresponding subtypes. Most genes from 17G-subtype1 directly participated in [for example, TNFRSF17, MEP1B, TNFRSF9, CST6, CANT1, IGF2BP1, IL13, LRP8 ( 62 71 )] or at least were relevant to [for example, PLXNC1, DUOX2, SLITRK3, ST6GAL2, F11 ( 72 77 )] inflammation and adaptive immune responses ( Supplementary Table 6 ), which were major physiological features of the pro-inflammatory subtype. Meanwhile, genes from 13G-subtype2 were related to down-regulation of inflammatory responses [for example, LIMD1, VSIG4, ADAMTS5, VTCN1 ( 78 81 )], blood vessel development [for example, VEGFD, RLN2, KLK12, and ANGPTL3 ( 82 86 )], and maladaptive responses to reduced cardiac functions [for example, VEGFD, ANGPTL3, LIMD1, VSIG4, IDI2 ( 79 , 83 88 ) ( Supplementary Table 6 ), which were physiological features related to M2 macrophage ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Literature review also indicated that functions of 17G-subtype1 and 13G-subtype2 were related to features of their corresponding subtypes. Most genes from 17G-subtype1 directly participated in [for example, TNFRSF17, MEP1B, TNFRSF9, CST6, CANT1, IGF2BP1, IL13, LRP8 ( 62 71 )] or at least were relevant to [for example, PLXNC1, DUOX2, SLITRK3, ST6GAL2, F11 ( 72 77 )] inflammation and adaptive immune responses ( Supplementary Table 6 ), which were major physiological features of the pro-inflammatory subtype. Meanwhile, genes from 13G-subtype2 were related to down-regulation of inflammatory responses [for example, LIMD1, VSIG4, ADAMTS5, VTCN1 ( 78 81 )], blood vessel development [for example, VEGFD, RLN2, KLK12, and ANGPTL3 ( 82 86 )], and maladaptive responses to reduced cardiac functions [for example, VEGFD, ANGPTL3, LIMD1, VSIG4, IDI2 ( 79 , 83 88 ) ( Supplementary Table 6 ), which were physiological features related to M2 macrophage ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…36 Additionally, a recent Mendelian randomization analysis provided evidence of a causal relationship between elevated MC and decreased LC and the deposition of abnormal cardiac proteins, which are known to be significantly associated with the occurrence of conduction blocks. 37,38 Overall, the precise mechanisms underlying the association between high MLR and increased risk of CCB are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Both SNPs used to instrument MM risk were also associated with amyloidosis (rs555992394) and had evidence for having an effect on blood cell counts including lymphocyte count and red cell distribution width (rs8141529) in the pheWAS analysis. These effects may be part of the shared causal pathway rather than pleiotropic given that amyloidosis and MM both share the precursor condition, MGUS [55], and that MM is known to have an effect on blood cell counts through myelosuppression [56].…”
Section: Causal Effects Of Circulating Proteins On MM Riskmentioning
confidence: 99%